Supply Chain Operational Reference untuk Perancangan Indikator Kinerja Rantai Pasok Farmasi - Yelita Anggiane Iskandar (Institut Transportasi dan Logistik Trisakti, 2022)
Warehouses have an important role in the supply chain. The pharmaceutical industry is no exception. Pharmacy Warehouse functions as a place to store drugs and medical devices before being distributed to health facilities such as community health centers, clinics, and hospitals. One of the Pharmacy Warehouse Technical Implementation Units located in Dairi Regency, North Sumatra, has several problems that occur along its supply chain. These problems, among others, are related to time, cost, and the number of products shipped. In addition, there was also an increase in aggregate demand for drugs and medical devices in 2018-2019. This increase in demand reinforces the need for designing pharmaceutical supply chain performance measurements. In designing the supply chain performance measurement, the framework used is the Supply Chain Operational Reference (SCOR) which includes the plan, source, make, delivery, and return processes, which are then translated into a number of criteria based on the attributes of reliability, responsiveness, agility, costs, and assets to a number of Key Performance Indicators (KPI). In weighting KPI, the method used is Analytical Hierarchy Process (AHP). Based on data processing and analysis, a supply chain performance measurement design was obtained with 11 performance indicators. Based on the AHP results, it was found that the highest weight value of 0.750 was obtained on the indicators of accuracy and delivery speed, while the lowest weight value of 0.117 was obtained on the order picking accuracy indicator.